Annual Report 1904-5 - Alden, John D.; Engineers Joint Council, New York, NY. Engineering Manpower Commission ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1905)
This annual report of the Engineering Manpower Commission summarizes the general operations and activities of the organization during 1969. The commission views its functions as three-fold, namely (1) promoting effective utilization of engineers in the national interest, (2) developing and evaluating information on the supply, demand, and compensation of engineers, and (3) establishing public understanding of engineering and its importance to the national economy. In pursuit of these objectives, the Commission has, in 1969, conducted and published several surveys on engineering manpower, salaries and income of engineers and technicians, and on the demand for engineers and technicians. Bulletins and articles by Commission personnel are listed. The program for 1970 is presented. The report concludes with a list of Commissioners, staff, and contributors to the Commission. (LC)
Microfiche.
Keywords: Industry; Information Services; Labor Utilization; Occupational Surveys; Annual Reports; Budgets; Engineering; Publications; Engineering Manpower Commission